The Effect of Acupressure on Decreasing Nausea and Vomiting in Pregnant Women in Midwives Independent Practice Sidoarjo - Handayani, Nanik; Anggasari, Yasi (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The study aimed to analyze the effect of acupressure on reducing nausea and vomiting in pregnant women. The method of this study used Quasy-Experiment. The instrument used acupressure SOP and Score Pregnancy Unique Quantification of Emesis and or Nausea Scoring System (PUQE). The statistical test used the Wilcoxon and Mann Whitney test. The results of the study in the treatment group after being given an acupressure are 9 people have decreased degree of nausea and vomiting. The results of the test using the Wilcoxon-test showed significance value of p = 0.00 (p-value <0.05) so that H0 was rejected, meaning that acupressure affected reducing nausea and vomiting. Meanwhile, in the control group 10 people had the same post-test and pre-test scores. The results of the Wilcoxon-test significance value p = 0.679 (p-value> 0.05), meaning that there is no effect of acupressure on reducing nausea and vomiting